2021
DOI: 10.7554/elife.66014
|View full text |Cite
|
Sign up to set email alerts
|

Competitive binding of STATs to receptor phospho-Tyr motifs accounts for altered cytokine responses

Abstract: Cytokines elicit pleiotropic and non-redundant activities despite strong overlap in their usage of receptors, JAKs and STATs molecules. We use IL-6 and IL-27 to ask how two cytokines activating the same signaling pathway have different biological roles. We found that IL-27 induces more sustained STAT1 phosphorylation than IL-6, with the two cytokines inducing comparable levels of STAT3 phosphorylation. Mathematical and statistical modelling of IL-6 and IL-27 signaling identified STAT3 binding to GP130, and STA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 102 publications
0
26
0
Order By: Relevance
“…IL-27 signals through dimerization of the cognate receptor IL-27Rα and the shared receptor GP130 25 . Current models for the assembly of complexes mediated by IL-27 have been largely based on structural principles derived from the IL-12/IL-23 or IL-6 systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-27 signals through dimerization of the cognate receptor IL-27Rα and the shared receptor GP130 25 . Current models for the assembly of complexes mediated by IL-27 have been largely based on structural principles derived from the IL-12/IL-23 or IL-6 systems.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome challenges in cytokine stability, we engineered an IL-27 cytokine variant in which the two monomeric components (EBI3 and p28) were fused by a short linker 25 . The fusion cytokine was expressed in insect cells and purified together with Domains 1-3 (D1, D2, D3) of GP130 and the first two domains of IL-27Rα (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IL-27 signals through a receptor complex consisting of IL-27Rα (TCCR/WSX-1) and gp130 expressed predominantly on T cells and NK cells (Pflanz et al, 2002, 2004) (Figure 1A). Binding of IL-27 to its receptor subunits triggers the activation of receptor-associated Janus Kinase 1 (JAK1) and JAK2 leading to phosphorylation of STAT1 and STAT3 (Lucas et al, 2003; Owaki et al, 2008; Wilmes et al, 2021). Functionally, IL-27 signaling serves to constrain inflammation by antagonizing differentiation of pro-inflammatory Th17 cells (Stumhofer et al, 2006), stimulating T-bet expression in regulatory T cells (Tregs) (Hall et al, 2012), and inducing production of the anti-inflammatory cytokine IL-10 (Stumhofer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, combining experimental work with mathematical methods has been a successful approach to gain quantitative insights into Th cell dynamics and decision-making (9)(10)(11)(12)(13)(14)(15). Notably, it was found that although signal integration via cytokines is transient and stochastic (16,17), the resulting decisions regarding the generation of T cell phenotypes, including selective cytokine secretion, are remarkably stable even in quantitative terms at the single-cell level (10).…”
Section: Introductionmentioning
confidence: 99%